2004
DOI: 10.1086/382353
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Mass Constraints on Low‐Mass Pre–Main‐Sequence Stellar Evolutionary Tracks: An Eclipsing Binary in Orion with a 1.0 M Primary and a 0.7 M Secondary

Abstract: We report the discovery of a double-lined, spectroscopic, eclipsing binary in the Orion star-forming region. We analyze the system spectroscopically and photometrically to empirically determine precise, distance-independent masses, radii, effective temperatures, and luminosities for both components. The measured masses for the primary and secondary, accurate to ∼ 1%, are 1.01 M ⊙ and 0.73 M ⊙ , respectively; thus the primary is a definitive pre-main-sequence solar analog, and the secondary is the lowestmass st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
92
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 51 publications
8
92
0
Order By: Relevance
“…For example, Siess et al (1999) found in their stellar evolution calculations that accretion reduces the efficiency of convection. This theoretical result agrees with another finding based on comparison of orbital masses of PMS stars with evolution models by Stassun et al (2004b), who found that TTSs seem to have lower convection efficiencies than MS stars. The reduced convection efficiency may lead to weaker dynamo action.…”
Section: The Suppression Of X-ray Emission By Accretionsupporting
confidence: 92%
“…For example, Siess et al (1999) found in their stellar evolution calculations that accretion reduces the efficiency of convection. This theoretical result agrees with another finding based on comparison of orbital masses of PMS stars with evolution models by Stassun et al (2004b), who found that TTSs seem to have lower convection efficiencies than MS stars. The reduced convection efficiency may lead to weaker dynamo action.…”
Section: The Suppression Of X-ray Emission By Accretionsupporting
confidence: 92%
“…In this respect, the progresses in 2D and 3D radiative hydrodynamical simulations of convection in the past decade (Ludwig et al 1999;Trampedach et al 1999;Trampedach 2007) provided evidence of both variations in α, which can depends on both T eff and log g, and the possibility of theoretically calibrating the mixing length parameter (see also . Moreover, there appears to be a lower efficiency of the superadiabatic convection in lowmass stars (α ≈ 1) with respect to the solar-calibrated one according to observations of some binary systems (see e.g., Simon et al 2000;Steffen et al 2001;Stassun et al 2004), and 7 Li data of young open clusters (Ventura et al 1998;D'Antona & Montalbán 2003).…”
Section: Convectionmentioning
confidence: 95%
“…Stassun et al 2004;Boden et al 2005). The results obtained so far are rather ambiguous, and reveal the difficulty in finding a unique description of convection, holding in all cases.…”
Section: Introductionmentioning
confidence: 90%
“…α = 1. Stassun et al (2004) also found that models with inefficient convection in the interior should be preferred. In the case of the binary components of V1174Ori they found a very good agreement with the models by Montalban et al (2004), employing the FST convection both in the interior and in the atmospheres computed by Heiter et al (2002).…”
Section: Introductionmentioning
confidence: 98%